Real Time Scanning-Modeling System for Architecture Design and Construction - Zhang, Ye; Zhang, Kun; Chen, Kaidi; Xu, Zhen (Advances in Technology Innovation, 2020)
The disconnection between architectural form and materiality has become an important issue in recent years. Architectural form is mainly decided by the designer, while material data is often treated as an afterthought which doesn’t factor in decision-making directly. This study proposes a new, real-time scanning-modeling system for computational design and autonomous robotic construction. By using cameras to scan the raw materials, this system would get related data and build 3D models in real time. These data would be used by a computer to calculate rational outcomes and help a robot make decisions about its construction paths and methods. The result of an application pavilion shows that data of raw materials, architectural design, and robotic construction can be integrated into a digital chain. The method and gain of the material-oriented design approach are discussed and future research on using different source materials is laid out.